Lewis and Clark among the Nez Perce : strangers in the Land of the Nimiipuu - Pinkham, Allen (The Dakota Institute Press of the Lewis & Clark Fort Mandan Foundation, 2013)
Lewis and Clark Among the Nez Perce is a generous and careful re-evaluation of what we all thought we knew about Lewis and Clark west of the Bitterroot Mountains. It is also a template for a series of tribal histories of the Lewis and Clark expedition that will be inspired by this book. Incidents we thought we knew backwards and forwards suddenly take on a new light when the historical lens is reversed, and the reader begins to understand what the extended visit of Lewis and Clark meant to their hosts--approximately four months of daily interchange with a community of Indians the white visitors regarded as especially friendly, hospitable, and helpful to the success of the expedition.--From publisher's description.